Dampak Perilaku Machivellian dan Equity Sensitivity Terhadap Persepsi Etis Mahasiswa Akuntansi (Studi Pada Mahasiswa Prodi Akuntansi Manajemen Politeknik Negeri Malang) - Kurnia Ekasari; Kartika Dewi Sri Susilowati; Putri Navalina, Ivana Larasati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of this study to determine the effect of machiavellian and equity sensitivity on ethical perception of accounting students in State Polytechnic of Malang.. The population used in this study were students of accounting management in State Polytechnic of Malang. The sample selection was determined using the purposive sampling method. Based on this method, 209 students were sampled from 1654 population numbers. To test the hypothesis, the researcher used multiple linear regression analysis by using SPSS 16.0. The results of analysis with multiple linear regression methods show that Machiavellian has a positive effect on ethical perception of accounting students. Equity Sensitivity has a positive effect on ethical perception of accounting students. Jointly tested, machiavellian and equity sensitivity have affect on ethical perception of accounting students.